Lukas: A Novella Revealing Low Socioeconomic Condition as a Risk Factor of Schizophrenia - Nicholas Valentino Handoko; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Recent world crises have caused millions to relocate. However, upon reaching their destination, immigrants often suffer from mental health problems. This work addresses how an immigrant status increases one’s likelihood to develop the early symptoms of schizophrenia and how to recover. It does so by using Blair Wheaton’s theory of the sociogenesis of psychological disorder and a phenomenological and participatory research written by Larry Davidson and his colleagues. It warrants a publication of the phenomenon in a creative form. This novella explores the perspective of Lukas Bertram, a wanted politician who left Earth for the planet of Morael, where he would try to survive amidst discrimination, give up, succumb to schizophrenia, and eventually recover. According to the findings, Lukas’ fatalism became the mediating variable between low socioeconomic status and his initial development of schizophrenia. Overcoming fatalism by reestablishing social connection and sense of control, thus, sparked his recovery process.